Utilization Of Surian Wood Shavings Waste Extract on Prima Mori Cotton Dyeing Results with Tunjung Mordant - Wijaya, Nadiva (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
This research is motivated as an effort made to obtain environmentally friendly textile dyes by utilizing surian wood shavings waste extract. The purpose of this study is to describe the color name (hue), color evenness, and color fastness to washing of surian wood shavings waste dyeing results on prime cotton. Experimental research uses primary data. Data collection using questionnaires from 15 panelists. Data were analyzed using the Mann Whitney Test using SPSS version 26. The results of the color name of the dyeing without mordant 87% Dark Salmon Pink code #D78D68 color evenness is very even, the results of color fastness without mordant 1 wash 73% color slightly changed, 2 washes 53% color slightly changed, and 3 washes 47% color slightly changed. The results of the tunjung mordant color 80% Gray code #574F4C color evenness is even, the results of the tunjung mordant color fastness 1 wash 80% the color changes slightly, 2 washes 67% the color changes slightly, 3 washes 60% the color changes slightly. The results of the Mann Whitney Test for color evenness were obtained .389> 0.05, Ho was accepted indicating that there was no significant difference in color evenness in the results of dyeing surian wood shavings waste extract on prima cotton mori. While color fastness obtained .547 > 0.05, Ho is accepted indicating that there is no significant difference in color fastness.